TI_GERICHTE 16.2005.129 vom 6. März 2006 , ordinaria trattata quale sommaria - definizione riconoscimento di debito - TI Tribunale d'appello (2006)
ordinaria trattata quale sommaria - definizione riconoscimento di debito